Outcomes for children with acquired brain injury (ABI) admitted to acute neurorehabilitation. (10th March 2021) - Keetley, Rachel; Bennett, Emily; Williams, Jane; Stewart, Iain; Whitehouse, William P; Pilling, Pauline; Manning, Joseph C
Abstract : Aim: To evaluate an innovative paediatric neurorehabilitation model in relation to improving quality of neurorehabilitation and reducing length of stay (LOS) for children with acquired brain injury. Method: A process evaluation approach was conducted in line with Medical Research Council evaluation of complex interventions guidance. Analysis was conducted on routinely collected patient data from 2017 to 2018, including LOS and family feedback. Descriptive and inferential statistics were used for quantitative analysis and qualitative data was analysed thematically. Results: Outcomes for 70 children (0–16y, median age 5y, IQR 1–11y, 46 males, 24 females) referred to the service indicated improved function and reduced complexity of need. The mean LOS was 10.6 days compared to baseline mean LOS of 41 days (2011–2012). High satisfaction from the families was recorded; however, ongoing needs and service gaps regarding long‐term support were identified. Interpretation: This service model is effective in delivering quality paediatric neurorehabilitation, demonstrating a sustained impact on LOS, and positive patient outcome data and family feedback for this group of patients. What this paper adds Investment in early intensive neurorehabilitation and supported discharge impacts length of stay (LOS) for children with acquired brain injury. Early intensive neurorehabilitation and supported discharge is effective. This is demonstrated by a sustained reduction in LOS, positive patient outcomes, and family feedback. What this paper adds: Investment in early intensive neurorehabilitation and supported discharge impacts length of stay (LOS) for children with acquired brain injury. Early intensive neurorehabilitation and supported discharge is effective. This is demonstrated by a sustained reduction in LOS, positive patient outcomes, and family feedback. This article is commented on by Lam Wai Shun, Swaine, and Bottari on page 764 of this issue.